Tuberculosis Outbreak Associated With Delayed Diagnosis and Long Infectious Periods in Rural Arkansas, 2010-2018. (January 2022) - Labuda, Sarah M.; McDaniel, Clinton J.; Talwar, Amish; Braumuller, Anthwan; Parker, Sarah; McGaha, Stephanie; Blissett, Carolynne; Wortham, Jonathan M.; Mukasa, Leonard; Stewart, Rebekah J.
Objectives: During 2010-2018, the Arkansas Department of Health reported 21 genotype-matched cases of tuberculosis (TB) among residents of a rural county in Arkansas with a low incidence of TB and in nearby counties. The Arkansas Department of Health and the Centers for Disease Control and Prevention investigated to determine the extent of TB transmission and provide recommendations for TB control. Methods: We reviewed medical and public health records, interviewed patients, and reviewed patients' social media posts to describe patient characteristics, identify epidemiologic links, and establish likely chains of transmission. Results: We identified 21 cases; 11 reported during 2010-2013 and 10 during 2016-2018. All case patients were US-born non-Hispanic Black people. Eighteen case patients had the outbreak genotype, and 3 clinically diagnosed (non–culture-confirmed) case patients had epidemiologic links to patients with the outbreak genotype. Social media reviews revealed epidemiologic links among 10 case patients not previously disclosed during interviews. Eight case patients (38%) had ≥1 health care visit during their infectious period, and 7 patients had estimated infectious periods of >12 months. Conclusions: Delayed diagnoses and prolonged infectiousness led to TB transmission in this rural community. TB education and awareness is critical to reducing transmission, morbidity, and mortality, especially in areas where health care providers have limited TB experience. Use of social media can help elucidate people at risk, especially when traditional TB investigation techniques are insufficient.